Improving livelihoods and reducing outmigration from the Northern Triangle in Central America: The potential role of cash transfers in expanded social safety nets - Díaz-Bonilla, Eugenio; Centurión, Miriam (International Food Policy Research Institute, 2022)
In 2019 almost 45 million immigrants lived in the United States, or about 13.7% of the total population, approaching the record high of 14.8% in 1890. Of that total, about 77% are lawful residents (either nat-uralized, permanent residents, or temporary residents), and the difference (about 23% or 11 million per-sons) are illegal immigrants. Both in the case of legal and illegal immigrants, the largest percentage is from Mexico (24% of the legal immigrants and somewhat less than 50% of the illegal ones, but those percentages have been declining since the mid-2000s). About 20% of the illegal immigration living in the US in 2017 came from Central America, principally El Salvador, Honduras and Guatemala (Ameri-can Immigration Council, 2021 and Passel and D’Vera Cohn, 2019). Overall, these three countries are the origin of about 3.3 million immigrants (legal and illegal) in the US in 2019 (Babich and Batalova, 2021).